Harmonisasi Tradisi Dan Modernitas Dalam Metodologi Pendidikan Islam KH. Hasyim Asy’ari - Ferdiansyah, Aldi; Haris, Yogi Sopian; Syarqowi, Muhammad (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
Islamic education is often faced with the dichotomy between preserving classical traditions and integrating modern science. KH. Hasyim Asy'ari responded to this challenge by developing an educational method that harmonized both, particularly at the Tebuireng Islamic Boarding School. This research employs a hermeneutical, historical-analytical approach based on a literature review of his works and thoughts. The research results indicate that KH. Hasyim Asy'ari did not completely reject modernity, but rather synthesized traditional Islamic values with the demands of the times. The classical system is maintained through the teaching of yellow books and methods such as sorogan and bandongan, while reforms are made by incorporating general subjects like mathematics, history, and foreign languages. Learning methods also evolved to be more participatory, such as discussions and debates. The establishment of Madrasah Salafiyah is proof of the integration of religious and general education. In conclusion, KH. Hasyim Asy'ari successfully formulated an integrative and relevant model of Islamic education for the times.an integrative and relevant model of Islamic education for the times.